Final answer:
To find the vertices of A’B’C’, apply the given translation rules to the coordinates of the original vertices.
Step-by-step explanation:
To find the vertices of A’B’C’ after applying the given translation rules, we need to apply each rule to the coordinates of the original vertices.
a. (x, y) → (x – 2, y – 7)
- A’ = (-6 - 2, -7 - 7) = (-8, -14)
- B’ = (-3 - 2, -1 - 7) = (-5, -8)
- C’ = (-5 - 2, 2 - 7) = (-7, -5)
b. (x, y) → (x + 11, y + 4)
- A’ = (-6 + 11, -7 + 4) = (5, -3)
- B’ = (-3 + 11, -1 + 4) = (8, 3)
- C’ = (-5 + 11, 2 + 4) = (6, 6)
c. (x, y) → (x, y – 3)
- A’ = (-6, -7 - 3) = (-6, -10)
- B’ = (-3, -1 - 3) = (-3, -4)
- C’ = (-5, 2 - 3) = (-5, -1)